Inventarisasi Jenis Ikan Bakau Di Teluk Pangpang Taman Nasional Alas Purwo Banyuwangi - Rofiqoh Meita Asrul; Kurnia Tristi Indah Dwi; Fitri Nurmasari (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2020)
The forest of mangrove in the area of Pangpan Blok in Jati Papak TNAP have mangrove of the fores. There are many natural activity of fish in the forest of mangrove. Research carried to determine the types of mangrove fish, knowing the density and diversity of mangrove fish that were in the Gulf region Pangpang the block in Jati Papak Alas Purwo National Park. The research conducted was in May-June 2016. This type of research is quantitative descriptive. The workings are used in this research include determining the location, fish sampling, measurements of abiotic parameters. Analysis of the data used in quantitative indices which include the density and diversity of species. Based on the results of the study, the types of fish that was obtained in the Gulf region Pangpang the Block in Jati Papak Alas Purwo National Park is family and 6 species. The results of the highest density value is kind periothalamus sp to the value of density 4.92, density the lowest skor is kind sardinella longiceps with a density value of 0.56, and the value of the relative density (KR) is the highest of species with density values ​​(kr) 1, 99 and density relative value (KR) sardinella longiceps lowest with a value of 0.23. The results of the analysis of mangrove fish diversity at every station indicate that the diversity of fish species Pangpang Gulf region the Block in Papak Alas Purwo National Park is relatively low, at station 1 value ranging between H ': 0.36645 at station 2 values ​​ranged between H': 0 , 35 934 and in satasiun 3 values ​​ranged between H ': 0.36266.